Recursive algorithm to directly obtain the sum of correlations in a CSS - de Marziani, Carlos Manuel (2011)
This paper presents a new recursive algorithm to directly obtain the sum of the autocorrelation functions of the M sequences belonging to a Complementary Set of Sequences (M-CSS). The proposed algorithm allows a digital filter with only one stage to be obtained, what significantly reduces the total number of memory requirements, multiplications and additions to be performed in comparison with the use of M correlators, even when these correlators could have an efficient implementation. The use of this algorithm can be of great relevancy since there is an increasing interest in the use of CSS (or derived sequences such as Loosely SynchronizedLS-sequences or Zero Correlation ZoneZCZ-sequences) in the field of communications and sensor systems.